Giving students a say : smarter assessment practices to empower and engage - Dueck, Myron; Hattie, John. (Alexandria, Va. : ASCD, 2021)
"This practical, engaging guide explores how student-centered assessment not only improves student engagement and achievement but also ensures that assessment is accurate, meaningful, and fair"--Provided by publisher.
Includes bibliographical references (p. 173-179) and index.
Professional.
Professional
Keywords: Educational evaluation -- United States; Educational tests and measurements -- United States; Grading and marking (Students) -- United States; Educational evaluation -- United States; Educational tests and measurements -- United States; Grading and marking (Education).; Instructional and educational works